PERLINDUNGAN HUKUM TERHADAP MASYARAKAT ATAS PENCEMARAN LIMBAH RUMAH TANGGA DI KOTA TANGGERANG SELATAN - Endi Suhadi; La Ode Risman; Bima Helpin Satria; Iman Alirahman (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
SITUATION ANALYSIS, Pondok Cabe Udik is a village located in the Pamulang sub-district in South Tangerang City, Banten Province, Indonesia. Before South Tangerang City became an autonomous city, Pamulang was one of the sub-districts of Tangerang Regency. Pondok Cabe Udik Village has a total population of 20,729 and has RW 14 and RT 74 while its area is 420 Ha. South Tangerang City has more than 55 companies and factories and besides that, the population density continues to increase every year. Especially for the Pondok Cabe Udik Village environment, there is an increase in the number of residents by 20,729, not to mention the presence of companies and factories will also increase even though they are still relatively small in number. The South Tangerang City Government has aspirations in realizing economic development and growth, and is committed to managing, protecting and regulating the socio-economic life of the surrounding community with a healthy, clean and good environmental perspective.